Network vulnerability assessment identify security loopholes in your network's infrastructure - Rahalkar, Sagar (Packt Publishing, 2018)
Being able to identify security loopholes has become critical to many businesses. That's where learning network security assessment becomes very important. This book will not only show you how to find out the system vulnerabilities but also help you build a network security threat model.